Smart Blind Stick With Emergency Button Using Internet Of Things (IoT) - Jamila Sahira, Junaiddi (2023)
A blind person finds it difficult to detect the presence of any obstacles in their path while moving from one location to another. Aside from that, the existing system has a lot of limitations such as do not have an emergency button and GPS. As a result, the Smart Blind Stick with Emergency Button using the Internet of Things (IoT) is proposed as a solution to assist visually impaired people in their day-to-day living without the assistance of others. The motivation to develop this proposed project is because there is no initiative for blind people to feel safe when they walk outside without guardians. An ultrasonic sensor, water sensor, emergency button and GPS module are used in this project. The blind stick is equipped with ultrasonic sensor to detect any obstacles in a range of 50 centimeters in front of blind people and a water sensor is attached under the blind stick to detect presence of water and wet surfaces. Then, the buzzer assists blind people in locating the exact obstacles and the wet surface area in front of them using a buzzer. The NodeMCU is used as the controller. Furthermore, because blind people cannot see the road, they are more likely to become lost. With the using of GPS tracker, the guardian can track the location of the blind people. So, with the GPS on the stick, the guardian will no longer be afraid about blind people and will be able to track their location. Aside from that, if blind people are in an emergency, they can press the emergency button on their stick, and the guardian will receive an alert notification, which will appear on the Blynk Application. The data is transmitted through the Wi-Fi module which is NodeMCU board. The location of blind people will send to the Blynk application, and it will display in the Blynk application. The Rapid Application Development (RAD) methodology is used as a guidance to complete the proposed system from the requirement planning phase to the system deployment phase. At the end, the objectives of proposed system are met, and the functionality of the system should be able to detect the obstacles and the wet surface area and able to send the alert notification and location of the blind people to the Blynk applications.